Extrafoveal Müller cells detection in vivo in the human retina: A pilot study based on optical coherence tomography. (October 2020) - Arrigo, Alessandro; Perra, Cristian; Aragona, Emanuela; Giusto, Daniele; Doglioni, Claudio; Pierro, Luisa; Giordano Resti, Antonio; Bandello, Francesco; Battaglia Parodi, Maurizio
Abstract: Müller cells (MC) represent a key element for the metabolic and functional regulation of the vertebrate retina. The aim of the present study was to test the feasibility of a new method for the in-vivo detection and quantification of extrafoveal MC in human retina. We developed a new approach to isolate and analyse extrafoveal MC in vivo, starting from structural optical coherence tomography data. Our pilot investigation was based on the optical properties of MC, which are known to not interfere with the light reaching the outer retinal structures. We reconstructed MC in the macular region of 18 healthy subjects and the quantitative analyses revealed ~42, 000/9 mm 2 cells detected. Furthermore, we included 2 patients affected by peripheral intraocular melanoma, with macular sparing, needing surgical enucleation. We used these two eyes to perform a qualitative comparison between our reconstructions and histological findings. Our study represents the first pilot investigation dedicated on the non-invasive isolation and quantification of MC, in-vivo, in human retina. Although we are aware that our study has several limitations, first of all related with the proper detection of foveal MC, because of the peculiar z-shape morphology, this approach may open new opportunities for the non-invasive in vivo analysis of MC, providing also potential useful perspectives in retinal diseases. Highlights: We developed a non-invasive quantitative approach to detect and quantify extrafoveal Müller cells in vivo in human retina. The Müller cells imaging morphology disclosed a good matching with histologic analysis. The macular Müller cell density was of ~42, 000/9 mm 2 .